Exploring the Role of Natural Agents in the Management of Diabetic-Induced Neuropathy - Darshan Anil Sonawane; Sunil K Mahajan; Chandrashekhar Patil; Durgesh Pagar; Gaurav Kasar (Asian Journal of Pharmaceutical Research and Development, 2025)
Nephropathy, retinopathy, cardiomyopathy, and peripheral neuropathy are some of the most common and serious complications of diabetes mellitus (DM), affecting around 50% of patients. These issues often arise due to poor blood sugar control or inadequate management of diabetes. Among these, diabetic peripheral neuropathy (DPN) is particularly troubling, as it’s not only widespread but also the most painful. This work aims to explore the various approaches used to manage DPN, from traditional treatments to more alternative options. We’ll dive into common medications, comparing the effectiveness of gabapentin and pregabalin, which are often used when regular painkillers like NSAIDs or opioids don’t work. We’ll also look at the wisdom of Oriental Medicine, which offers unique perspectives, and examine the potential of natural compounds that researchers suggest could be effective either alone or alongside current treatments. Lastly, we’ll discuss ancient practices like acupuncture and electrostimulation as potential non-drug alternatives that may provide relief for those suffering from DPN.